The Impact of the COVID-19 Pandemic on the Tourism Industry of Kazakhstan - BERDIBEKOV, Dauren; LASHKAREVA, Olga; MAIDYROVA, Aigul (Journal of Environmental Management and Tourism, 2023)
This article aims to examine the impact of the COVID-19 pandemic on the tourism industry in the Republic of Kazakhstan, which has been identified as a particularly vulnerable sector. The paper, in which Pearson correlation analyses was used, is significant in understanding the aftermath of the pandemic on the tourism industry in Kazakhstan, and how it compares to global trends. The study's results demonstrate that the consequences of the pandemic on the tourism industry in Kazakhstan are similar to those worldwide. However, the research also highlights a positive sign of recovery for domestic tourism in Kazakhstan, where the number of domestic tourists has surpassed pre-pandemic levels. This article's contributions are to provide valuable insights into the effects of COVID-19 on the tourism industry in Kazakhstan, and it can serve as a helpful resource for policymakers in the country.